(untitled) (Philologia, 2021)
In a broad view, culture has two primary operative functions: one is to endorse the ‘fixed tablet of tradition’ and the second is to provide a location for the progression of culture through generations and time. This paper refers to the process of cultural change and hybridization, one way to distinguish between these two cultural forces is that fixed tradition is not geographically, whereas as hybridisation is often specifically related to place, locale and situation. The rhetoric of hybridity or the hybrid talk is associated with the emergence of postcolonial discourse and its critiques of cultural imperialism. This stage in the history of hybridity is characterised by literature and theory that focuses on the effects of mixture upon identity and culture. Cultural hybridity produces new forms of alterity and is inherent in processes of social and cultural dynamics. A sharp contrast between cultures and hybrids is the notion of choice in cultural referent. This choice is significant because in cultural hybrids, traditions are loosened, and the capacity to make choices allowed. Cultural hybridity therefore, represents a cultural dynamism. This ferment of culture is found on the borders, in the overlaps, and the in-between places between two or more cultures.